Relationship between anthropometric and strength variables and maximal throwing velocity in female junior handball players - a pilot study - Sarvestan, J.; Riedel, V.; Gonosova, Z.; Linduška, P.; Pridalová, M. (Acta Gymnica, 2019)
Background: Throwing velocity is one of the determinant scoring elements in handball. However, our knowledge of anthropometric factors and shoulder muscle strength among female players and how these affect throwing velocity is limited.